Implementasi Pengiriman Data Wireless dengan Metode Time Division Multiple Access dan Timing-Sync Protocol for Sensor Networks pada Kolam Ikan - Adi Pratama; Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Distributed data acquisition system for water quality of fishpond usually using conventional method. This method used microcontroller device for control system operations, sensor as data acquisition and wire as data medium. Monitoring System of water quality of fishpond using a microcontroller as control system for data processing from a lot of node-sensor at once time has disadvantages. There are many possibilities that distributed data from node-sensor to control system could be crashed. Wire as data medium has less efficiency at wider area, such as fishpond culture. This leads to the application of wireless communication system. The reason for using wireless communication instead of wire-use connection is more practical and making the installation simpler. A new aipproach to synchronize the time iis needed for seinsor networks. In thiis paper, we discuss about Timing-sync Protocoli for Sensor Networks (TPSN) and Time Division Multiple Access (TDMA) that aims at providiing network-wide time synchronization in a sensor network to avoid crashed data. In addition, this research also present wireless communication method using nRF24L01 module. As the result, we got that node client can distributed data acquisition for fishpond water in the amount of 18 bytes with the synchronized time without being crashed.